Second Five-Year Plan (1956-57 to 1960-61) Bombay State Government of Bombay Political and Services Department - Planning Commission (Planning Commission, 1956)
Planning is a continuous process of effective utilisation of resources, human and material, available to the community so as to obtain from them increased output of goods and services and to attain other social objectives like reduction in inequalities of income, wealth and opportunity. the primary objective of planning in India is to raise the standard of living of the people and to enlarge opportunities for a richer and more varied life. This involves a sustained and well directed effort spread over a long period. for a proper appreciation of the Second Five-Year Plan and the directions in which future development is indicated it is necessary, therefore, to have a brief idea of the state of economy at present and the lines on which development has steadily taken place so far.
Government of Bombay Political and Services Department